Group IIA secretory phospholipase 2 independently predicts mortality and positive blood culture in emergency department sepsis patients - Utsav Nandi; Alan E. Jones; Michael A. Puskarich (Journal of the American College of Emergency Physicians Open)
Abstract Objective The IIA isoform of phospholipase A2 is an acute phase reactant that increases in sepsis, although data regarding its prognostic value are limited. We hypothesized that group IIA secretory phospholipase A2 (sPLA2‐IIA) predicts sepsis mortality and positive cultures and sought to compare its predictive characteristics to lactate and procalcitonin. Methods sPLA2‐IIA and procalcitonin levels were measured at enrollment in emergency department patients with early severe sepsis and compared with lactate levels. The primary outcome was in‐hospital mortality. The secondary outcome was any positive culture with a sub‐group analysis of only blood‐culture positive patients. Optimum cut‐point was determined using receiver operating characteristics curves. A multivariable model was developed to test the independent prognostic value of elevated sPLA2‐IIA to predict mortality. Results Of the 192 patients in the cohort, 160, 153, and 158 had samples available for analysis of sPLA2‐IIA, procalcitonin, and lactate, respectively. A total of 21% of patients met the primary outcome of in‐hospital mortality. At a 100 ng/mL threshold for sPLA2‐IIA, adjusted odds to predict mortality were 3.78 (95% confidence interval = 1.14–12.56, P = 0.03). sPLA2‐IIA and procalcitonin were both elevated in culture‐positive patients; however, the difference was not statistically significant. sPLA2‐IIA was significantly higher in blood culture‐positive patients. Conclusion An elevated level of sPLA2‐IIA was associated with increased mortality in sepsis patients. sPLA2‐IIA levels, unlike procalcitonin, also were significantly higher in blood culture‐positive patients.